2012
DOI: 10.1096/fj.12-208868
|View full text |Cite
|
Sign up to set email alerts
|

Timed high‐fat diet resets circadian metabolism and prevents obesity

Abstract: Disruption of circadian rhythms leads to obesity and metabolic disorders. Timed restricted feeding (RF) provides a time cue and resets the circadian clock, leading to better health. In contrast, a high-fat (HF) diet leads to disrupted circadian expression of metabolic factors and obesity. We tested whether long-term (18 wk) clock resetting by RF can attenuate the disruptive effects of diet-induced obesity. Analyses included liver clock gene expression, locomotor activity, blood glucose, metabolic markers, lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
303
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(342 citation statements)
references
References 41 publications
25
303
4
3
Order By: Relevance
“…Timed HF diet led to decreased body weight, cholesterol and TNFα levels and improved insulin sensitivity compared with mice fed HF diet ad libitum. Timed HF-fed mice exhibited a better satiated and less stressed phenotype of low ghrelin and corticosterone compared with mice fed timed low-fat diet [139]. In addition, timed HF diet improved metabolic pathway function and oscillations of the circadian clock and their target gene expression.…”
Section: Effect Of High-fat Diet On Circadian Rhythmsmentioning
confidence: 92%
See 2 more Smart Citations
“…Timed HF diet led to decreased body weight, cholesterol and TNFα levels and improved insulin sensitivity compared with mice fed HF diet ad libitum. Timed HF-fed mice exhibited a better satiated and less stressed phenotype of low ghrelin and corticosterone compared with mice fed timed low-fat diet [139]. In addition, timed HF diet improved metabolic pathway function and oscillations of the circadian clock and their target gene expression.…”
Section: Effect Of High-fat Diet On Circadian Rhythmsmentioning
confidence: 92%
“…It has recently been shown that long-term day-time RF can increase the amplitude of clock gene expression, increase expression of catabolic factors, and reduce the levels of disease markers leading to better health [138] (Figure 3). Moreover, timed high-fat diet led to reduced body weight and improved metabolism compared to animals that consumed the same caloric intake spread out throughout the day [139] (see below). Because timed feeding is dominant in resetting circadian rhythms even in animals with lesioned SCN, it has been suggested that there is a food-entrainable oscillator (FEO).…”
Section: Effect Of Restricted Feeding (Rf) On Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two recent studies have shown promising results which suggest that eating according to the same daily schedule can diminish HFD-induced obesity. Scheduled high-fat feedings for 8 h during the dark period (145) or for 4 h during the light period (146) without calorie restriction prevented obesity. These studies suggest that regulating the timing of food intake can improve the amplitude of the clock and clockcontrolled metabolic-related gene expression rhythms, nutrient utilization, energy expenditure, and insulin sensitivity.…”
Section: Food Timingmentioning
confidence: 99%
“…Investigaciones previas con animales de laboratorio han mostrado que el consumo de dietas altas en grasa afecta componentes que forman parte del sistema homeostático, como el ritmo circadiano (Honma, Hikosaka, Mochizuki & Goda, 2016;Sherman et al, 2012) y la actividad espontánea de los animales (Ludmilla et al, 2017). Por ejemplo, sujetos experimentales expuestos a una dieta alta en grasa presentaron un incremento inicial de la acumulación de tejido adiposo, sin que el peso corporal aumentara significativamente; sin embargo, después de tres semanas se encontró un aumento del peso corporal e hipertrofia de los adipocitos (La Fleur, Van Rozen, Luijendijk, Groeneweg & Adan, 2010;Woods, Seeley, Rushing, D'Alessio & Tso, 2003).…”
Section: Introductionunclassified